Nurse anesthesiology students’ perceptions of AI chatbot use in ESP learning - Susanta, I Putu Agus Endra; Suryati, Ni Wayan Novi; Dewi, Kadek Maya Cyntia; Rusanti, Putu; Susandi, Ni Kadek Ary; Wismadewi , I Gusti Agung Galuh (Indonesian Research Journal in Education |IRJE|, 2026)
This study examined nurse anesthesiology students’ perceptions of AI chatbot use in English for Specific Purposes (ESP) learning at ITEKES Bali. A descriptive quantitative survey was conducted with 105 sixth-semester students enrolled in the Diploma IV Nursing Anesthesiology Study Program. Data were collected using a 14-item questionnaire adapted from selected constructs of the Unified Theory of Acceptance and Use of Technology (UTAUT): performance expectancy, effort expectancy, social influence, facilitating conditions, and behavioral intention. The responses were analyzed using descriptive statistics. The overall mean score was 3.66, indicating a high level of acceptance. Facilitating conditions received the highest mean score (3.82), followed by Performance Expectancy (3.74), Effort Expectancy (3.65), Behavioral Intention (3.65), and Social Influence (3.29). These results indicate that students generally perceived AI chatbots as accessible and useful supplementary tools for learning medical terminology, practicing English in clinical situations, and supporting independent study. However, lecturer and peer encouragement remained comparatively limited.